Therapy response in seronegative versus seropositive autoimmune encephalitis - Berger, Benjamin; Hauck, Sophie; Runge, Kimon; Tebartz van Elst, Ludger; Rauer, Sebastian; Endres, Dominique (Frontiers in Immunology, 2023)
Background Autoimmune encephalitis (AE) might be seropositive or seronegative, depending on whether antibodies targeting well-characterized neuronal antigens can be detected or not. Since data on treatment efficacy in seronegative cases, are scarce, the main rationale of this study was to evaluate immunotherapy response in seronegative AE in comparison to seropositive cases. Methods An electronic database search retrospectively identified 150 AE patients, treated in our tertiary care university hospital between 2010 and 2020 with an AE. Therapy response was measured using both general impression and the modified Rankin Scale (mRS). Results Seventy-four AE patients (49.3%) were seronegative and 76 (50.7%) seropositive. These cases were followed up for a mean of 15.3 (standard deviation, SD, 24.9) and 24.3 months (SD 28.1), respectively. Both groups were largely similar on the basis of numerous clinical and paraclinical findings including cerebrospinal fluid, electroencephalography, magnetic resonance imaging, and 18-F-fluor-desoxy-glucose-positron-emmission-tomography pathologies. The majority of patients (80.4%) received at least one immunotherapy, which were glucocorticoids in most cases (76.4%). Therapy response on general impression was high with 49 (92.5%) of treated seronegative, and 57 (86.4%) of treated seropositive AE cases showing improvement following immunotherapies and not significantly different between both groups. Notably, the proportion of patients with a favorable neurological deficit (mRS 0-2) was twice as high during long-term follow-up as compared to baseline in both groups. Conclusion Since both, patients with seronegative and seropositive AE, substantially benefitted from immunotherapies, these should be considered in AE patients irrespective of their antibody results.